Perilaku Menyimpang Praktik Bisnis Periklanan dalam Perspektif Hukum Pidana dan Penegakan Hukumnya - Hanafi Amrani (Fakultas Hukum Universitas Islam Indonesia, 2016)
This research is aimed to analyze the criteria and form of deviation behaviour in business practice of advertisement and the deviation behaviour in business practice in the perspective of criminal law and its legal enforcement. This is a normative legal research using the regulation approach and concept approach. The data was collected and analysed using the descriptive – qualitative method. The result of the research showed that first; there are two criteria to show the deviation behaviour: fact of material and rationale consumers. Meanwhile, a number of deviations in presenting the information of advertisement through mass media including presenting the information falsely (false statement), revealing the fact misleadingly (mislead statement), giving the description incompletely (omission), giving the exaggerating opinion without any support of fact (puffery), and advertisement is contradicting with politeness, moral and ethics. Second, in the perspective of criminal law, the deviation behaviour can be categorized as the criminal act. The problem in this research is related to the legal enforcement particularly related to the unequal perception between society and the law enforcers in responding the deviation behaviour in the business practice of advertisement whether it is included in business tort or business crime. Other factor that is also impacting the enforcement of criminal law is related to the evidence, mentality of the law enforcers and society and political will of government in doing an action towards the business activity of deviating advertisement.